A Response to "Listening with Displacement". Issue 1 (1st June 2020) - Azar, Rihab
Abstract: Can collaborative, transparent, and open-ended inquiries empower social activism and grassroot change? In my response to "Listening with Displacement, " I argue that it can and that it should. In an age full of unhelpful and dangerous narratives of displacement, I suggest that anthropologists are very well-positioned to take their role a step further to facilitate social understanding and cohesion as they collaboratively explore and create points of contact with and for their subjects.